2019
DOI: 10.1016/j.molp.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of FLC by FLOWERING LOCUS T (FT) and FD through a 5′ FLC Promoter Region in Arabidopsis

Abstract: Recently, it was reported that the florigenic FT protein bound to a 3 0 region of the potent floral repressor FLC (FLOWERING LOCUS C) to activate the expression of long noncoding antisense RNAs known as COOLAIR and consequently repress FLC expression to control flowering time and seed dormancy in Arabidopsis (Chen and Penfield, 2018). Here, we show that FT represses FLC expression through a 5 0 promoter region, but not COOLAIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
1
35
0
3
Order By: Relevance
“…1B); instead, longer cold exposures of 8 and 12 wk were required for FT activation. In addition, it had previously been reported that FT feeds back to repress FLC at both vegetative and reproductive stages (Chen et al 2014;Chen and Penfield 2018;Luo et al 2019). Therefore, we wondered whether the lack of FT activation in Lov-1 after 4 wk of cold could explain FLC reactivation in that case and, more generally, the differences in the reactivation probability ( Fig.…”
Section: Ft Is Not Responsible For the Change In The Reactivation Promentioning
confidence: 91%
See 1 more Smart Citation
“…1B); instead, longer cold exposures of 8 and 12 wk were required for FT activation. In addition, it had previously been reported that FT feeds back to repress FLC at both vegetative and reproductive stages (Chen et al 2014;Chen and Penfield 2018;Luo et al 2019). Therefore, we wondered whether the lack of FT activation in Lov-1 after 4 wk of cold could explain FLC reactivation in that case and, more generally, the differences in the reactivation probability ( Fig.…”
Section: Ft Is Not Responsible For the Change In The Reactivation Promentioning
confidence: 91%
“…Thus, our data indicate that FT levels do not influence FLC epigenetic stability in Lov-1. Another possibility is that the Lov-1 polymorphisms could disrupt either or both of the previously reported FT-binding sites at FLC (Chen and Penfield 2018; Luo et al 2019). However, if FT was necessary for stable silencing of FLC, we would expect reactivation also in Col FRI in SD conditions where there is no FT.…”
Section: Ft Is Not Responsible For the Change In The Reactivation Promentioning
confidence: 97%
“…RNA binding proteins of the autonomous pathway function to process COOLAIR, a set of lncRNAs transcribed antisense of FLC (Swiezewski et al, 2009;Hornyik et al, 2010;Whittaker and Dean, 2017). The significance of these lncRNAs in the regulation of vernalization remains controversial (Helliwell et al, 2011;Luo et al, 2019); however, much data have been gathered to indicate a functional if not essential role. The physical association of COOLAIR with FLC chromatin is associated with the reduction of H3K36me3 and H3K4me3, rendering the chromatin inactive (Csorba et al, 2014;Fang et al, 2020).…”
Section: Epigenetic Regulation Of Flc-like Genes In Cerealsmentioning
confidence: 99%
“…The natural variation studies implicating a functional role for COOLAIR in FLC regulation have been followed up by transgene experiments designed to further explore the mechanism of COOLAIR action (Csorba et al 2014;Wang et al 2014;Rosa et al 2016). However, in some cases, studies of transgenes aimed at attenuating antisense expression have concluded that COOLAIR expression is not required for vernalization (Helliwell et al 2011;Li et al 2018;Luo et al 2019;Luo and He 2020). This led to the suggestion that COOLAIR functions in FLC regulation at warm temperatures but potentially not in the cold.…”
mentioning
confidence: 99%